A Systematic Study of Coumarin–Tetrazine Light‐Up Probes for Bioorthogonal Fluorescence Imaging. Issue 44 (14th July 2020) - Galeta, Juraj; Dzijak, Rastislav; Obořil, Jan; Dračínský, Martin; Vrabel, Milan
Abstract: Fluorescent probes that light‐up upon reaction with complementary bioorthogonal reagents are superior tools for no‐wash fluorogenic bioimaging applications. In this work, a thorough study is presented on a set of seventeen structurally diverse coumarin–tetrazine probes that produce fluorescent dyes with exceptional turn‐on ratios when reacted with trans ‐cyclooctene (TCO) and bicyclononyne (BCN) dienophiles. In general, formation of the fully aromatic pyridazine‐containing dyes resulting from the reaction with BCN was found superior in terms of fluorogenicity. However, evaluation of the probes in cellular imaging experiments revealed that other factors, such as reaction kinetics and good cell permeability, prevail over the fluorescence turn‐on properties. The best compound identified in this study showed excellent performance in live cell‐labeling experiments and enabled no‐wash fluorogenic imaging on a timescale of seconds. Abstract : Light on ! A series of seventeen coumarin–tetrazine probes that produce in reaction with trans ‐cyclooctene and bicyclononyne dienophile bright fluorophores were synthesized and evaluated in different bioimaging applications. These probes show excellent turn‐on properties and can be used for fast and selective bioorthogonal fluorescence labeling in live cells.